STATE RELATIONS, HUMAN RIGHTS AND WELFARE: CRITICISM OF TRADE STANDARDIZATION GOODS AND SERVICES - Suwardi, Suwardi (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
Trade is the main driver of development carried out to advance the general welfare as the goal of the country. The state as the executor of economic sovereignty is required to regulate the implementation of trade with due regard for human rights, including the right to obtain welfare. Law No. 7 of 2014 concerning Trade in force currently contains immoral material, namely provisions regarding the standardization of goods and services, as well as provisions concerning criminal acts related to the standardization. For this reason, it is necessary for the politics of legal development to amend trade laws by not including norms of standardization obligations, and to eliminate criminal threats for trading activities.